Exponential forecasting of the monthly volume of the tourism receipts in Bulgaria - Preslav Dimitrov; Maria Kalinova; Gantcho Gantchev; Chavdar Nikolov (Tourism & Management Studies)
In Compliance with the annual Act for the State Budget, the Bulgarian Ministry of Finance usually makes twice a year an internal budget restructuring in the budgets of the separate Ministries and State Agencies of the Bulgarian State. What is in intriguing in this internal budget restructuring is that it is usually done in the months when the tourism receipts in the form of Value Added Tax turnovers are usually accumulated by the Bulgarian the tax administration. The need of proper forecasts that could eventually justify or reject such a hidden harvesting policy has never been examined and put to the public attention. The present paper regards several major problems in the application of the exponential smoothing methods for the purpose of the long-run forecasting of the monthly volume of the tourism receipts in Bulgaria. These problems include: (i) the problem of determining the time series pattern; or the so-called “forecast profile”; (ii) the selection of a suitable forecasting method; (iii) Calculating of shortrun and long-run forecasts; (iv) the comparison of the results of the forecast techniques on the basis of the errors in the forecasts. As a result the Holt-Winters method is applied with the conclusion that the produced forecasts could trigger a process a more financially autonomous national tourism administration that will allow a greater part of the collected tax revenues for the tourism sector to be returned into the tourism industry in a form of public investments through this very same more autonomous national tourism administration.